Effects of co-chemotherapy ethyl acetate fraction of eurycoma longifolia jack roots and doxorubicin against apoptosis through expression p53 mutant and Bcl-2 - Galih Dwi Mulyati; Laela Hayu Nurani; Sitarina Widyarini (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background : It was found mutations of p53 gene in Breast cancer. Mutant p53 protein caused a decrease in cell apoptosis mechanisms through increased expression of Bcl-2. Breast cancer therapy is commonly used chemotherapy using Doxorubicin. However, effectiveness of the use of this chemotherapeutic agent is limited due to the emergence of side effects and toxic to normal cells. Therefore, it is necessary to develop new drugs for combination of chemotherapy. Eurycoma longifolia Jack roots has the potential as co-chemotherapy of breast cancer and it is not toxic to normal cells. Method : Rats were divided into 5 groups. Each group consisted of four female white Sprague Dawley rats. Group 1 (Normal), group 2 (DMBA 20 mg/kgB.W), group 3 (DMBA +Doxorubicin 1.12 mg/kgB.W), group 4 (DMBA +fractions 100 mg/kgB.W), group 5 (DMBA+Doxorubicin +fractions). All the rats were sacrificed at weeks 16 and to be taken their breast tissue. Immunohistochemistry was performed using a mouse monoclonal antibody mutant (BioGenex) and Bcl-2 (BIOSS). Results : expression of mutant p53 percentage obtained for group I (9.35 ± 0.32)%, II (21.65 ± 1.60)%, III (10.72 ± 2.52)%, IV (11.63 ± 3.39)%, V (12.72 ± 3.44)%, While the percentage of Bcl-2 expression obtained for I (20.62 ± 10.09)%, II (52.83 ± 3.61)%, III (24.38 ± 3.54)%, IV (38.01 ± 6.25)%, V (27.99 ± 4.27)%. The data was statistically tested by Kruskal Wallis test (p< 0.005). Conclussion : Co-chemotherapy of E. longifolia Jack roots and Doxorubicin can stimulate apoptosis through decreased in the expression of mutant p53 protein and Bcl-2 in breast tissue of rats induced by DMBA.